STUDY OF CHANGES IN MICROGRAVITY ANOMALY RESPONSES DUE TO CO2 INJECTION THROUGH RESERVOIR SIMULATION AT A DEPTH OF 620 M - Az Zahra, Fatimah
In the CCS (Carbon Capture Storage) project, subsurface monitoring needs to be done properly so that the injected CO2 can be safely stored in the reservoir. One geophysical method that can be used for subsurface monitoring is the gravity method. In its application, a synthetic model was created that considers depths of up to 620 meters using a homogeneous model with reservoir simulation parameters obtained from previous studies. Simulation modeling was carried out using CMG (Computer Modelling Group) 2021 software. 10. Based on the results of reservoir simulation modeling with the capacity of the reservoir to hold CO2 is 218.28.236 ????3 and the injection rate is 4013.4 ????3/day, the injection time in this study requires another 18 years after 20 years of injection so that CO2 can be stored fully. The anomalous response of microgravity obtained shows an increase as the volume of CO2 injection increases. Creation of time-lapse microgravity anomaly maps to determine microgravity anomalies at CO2 injection points after 3 years, 5 years, 10 years, and 20 years with a reservoir depth of 620 m. Weight-lapse anomaly values for the period 2000-2003 January, with a minimum value of 0.01241 ?Gal and a maximum of 2.711 ?Gal. Gravity anomaly values for the period 2000-2005 January, with a minimum value of 0.04587 ?Gal and a maximum of 4.528 ?Gal. Weight-lapse anomaly values for the period 2000-2010 January, with a minimum value of 2.003 ?Gal and a maximum of 48.97 ?Gal. Weight-lapse anomaly values for the period 2000-2020 January, with a minimum value of 5.317 ?Gal and a maximum of 64.75 ?Gal. Based on the analysis of curve patterns, the proposed interval of the gravitational survey station for monitoring the spread of CO2 in anomalous waves in the period 2000-2003 January was worth 700 m and in the period 2000-2020 January was worth 1600 m.